Response of the stratified flow structure and energy production to the climate change effects in a Sea Strait: the case study of the Bosphorus - Altas, Furkan; Ozturk, Mehmet (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
The Bosphorus has a considerable energy potential due to its topography and environmental conditions. It is a non-tidal strait and characterized by a stratified flow structure, which could show high variability spatially and temporally. Therefore, unlike tidal channels, many processes and uncertainties should be considered for energy production in the Strait. In particular, the change of the driving forces in the future that determine the flow structure is a major uncertainty for energy production. This study aims to determine the energy production in the Bosphorus under the impact of climate change in the future. The extreme flow characteristics and energy production were identified considering two different climate change scenarios (RCP 2.6 and RCP 8.5). In the highenergy region of the Bosphorus, upper layer thickness projections vary from 15 m to 19 m, and Marine Current Turbines can operate 50-80 % of the year. The average annual energy production in the Bosphorus is projected to vary between 1.42 MW and 2.76 MW. Assuming that the maximum and minimum conditions will be equally distributed in the period up to 2100, an average annual energy production of similar to 2.1 MW will be realised in the Bosphorus through the sample MCT array.
Keywords: Stratified flow; MCTs; Renewable energy; Numerical modelling; Climate change; BLACK-SEA; ISTANBUL BOSPORUS; CURRENT TURBINES; WATER; FIELD; CURRENTS; IMPACTS; RIVER; GENERATION; ENSEMBLE; Science & Technology - Other Topics; Energy & Fuels